Microneedling and epidermal growth factor (EGF) as strategies for the acne scars treatment - Mônica Albuquerque Costa; Érika Santos Freire; Maria Cristina Vieira Andrade; Marcio Roberto Silva; Maria Christina Marques Nogueira Castañon; Nádia Rezende Barbosa Raposo (Sociedade Brasileira de Dermatologia (SBD), 2022)
The microneedling technique and the transdermal drug delivery are indicated to treat acne scars. Objective: Evaluation of the microneedling technique associated with the drug delivery of the epidermal growth factor (EGF). Methods: Randomized double-blind clinical trial of 30 patients divided into two groups: (1) - two microneedling sessions with a 30-day interval, (2) - two microneedling sessions with the same interval but associated with EGF drug delivery. The patients were evaluated clinically (global acne scarring grading system - Goodman and Baron) global acne scarring grading system via multispectral image and through self-perception questionnaires. The statistical analysis (Student T-test, SNK test, analysis of variance) was performed with the SisVar software (UFLA, 1996). Results: The groups were homogeneous regarding age, gender, and phototype. Clinical assessments showed a reduction in severity scores for both groups. The multispectral analysis revealed a decrease in porphyrins (p = 0.0296) and an improvement in skin texture in group two subjects. Conclusion: Microneedling therapy was effective and safe for the acne scars treatment, and EGF demonstrated to be a promising strategy as well.